Radiographic evaluation of posttraumatic osteoarthritis of the ankle: the Kellgren–Lawrence scale is reliable and correlates with clinical symptoms - Holzer, Nicolas; Salvo, Davide; Marijnissen, A.C.A; Vincken, K. L.; Che Ahmad, Aminudin; Sierra, E.; Hoffmeyer, Pierre; Stern, Richard; Lübbeke Wolff, Anne; Assal, Mathieu (Elsevier, 2015)
Summary Objective To assess reliability and construct validity of the Kellgren–Lawrence (K&L) scale in posttraumatic ankle osteoarthritis (OA); additionally evaluate the validity of including tibiotalar tilting in the scale.